2012
DOI: 10.1080/10934529.2012.672071
|View full text |Cite
|
Sign up to set email alerts
|

Age dependency on some physiological and biochemical parameters of male Wistar rats in controlled environment

Abstract: The aim of the study was to assess the age dependence on some physiological and serum chemistry parameters of male Wistar rats for the estimation of reference values in controlled environment. We are presenting values obtained from a large number of animals such as survival, average life span, body mass, food and water intake, serum chemistry parameters as total protein, albumin, transferrin and ferritin in serum. One part of this work compares the relationship between rat and human age. The maximal life span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
3
19
0
2
Order By: Relevance
“…As expected, sarcopenia decreased the gastrocnemius muscle mass according to other studies [17][18][19]. However, tumour evolution did not lead to a further reduction of gastrocnemius muscle mass but was associated with an accentuated decrease in body weight gain.…”
Section: Discussionsupporting
confidence: 84%
“…As expected, sarcopenia decreased the gastrocnemius muscle mass according to other studies [17][18][19]. However, tumour evolution did not lead to a further reduction of gastrocnemius muscle mass but was associated with an accentuated decrease in body weight gain.…”
Section: Discussionsupporting
confidence: 84%
“…Wirth and Nijal [22] and Calabrese [3] stated that chronic exposure to low doses of mercury can have an unpredictable course (but also consequences) and the body's response to low (subtoxic) doses may be different. Ništiar et al [9] and Shibutani et al [24] stated that the determining indicator of food intake (but also changes in weight and heavy metal intake) is water intake, which only partially corresponds to the results in this study. The opposite situation may also be the fact that food intake is limiting in this respect and water intake is derived from it.…”
Section: Physiological Parameterssupporting
confidence: 60%
“…Thus, the survival was 100% and at the same time it was confirmed that the applied dose is low chronic dose. In a lifelong experiment [9] evaluating the survival of animals exposed to cadmium, more individuals survived (one-year survival was also 100% as confirmed by the experiments) compared to other heavy metals. This may be because cadmium in low doses may function as an essential element [10][11][12].…”
Section: Toxicological Parametersmentioning
confidence: 53%
“…Data from final sessions were obtained from rats aged 6.11 ± 0.26 and 25.90 ± 0.28 months, respectively. This age of the older rats is considered equivalent to the human post‐reproductive period (60–70 years) and precedes the onset of accelerating mortality of this strain (Nistiar et al ., ).…”
Section: Resultsmentioning
confidence: 97%